Semiopragmatics of Roger Oden in the Context of the Modern Communicative Paradigm - Ivanova, Iva (Media and Language, 2018)
The article follows the evolution of R. Oden’s theoretical views related to the development of semiopragmatics as a scientific discipline exploring the peculiarities of communication. The author outlines his innovative views on the communicative process in a series of studies, the most prominent of which are „De la fiction “ (2000) and „Les Espaces de communication“ (2011). R. Oden examines the communication as a two-way process of text creation in which the producer and the recipient are equal participants. Another key point in semiopragmatic theory is the idea that the context should be regarded as the starting point for analyzing the process of producing meaning. R. Oden’s recent scientific research is related to the introduction of the concept of mental communication space in the study of audiovisual communication through a mobile phone.